The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2012
DOI: 10.1590/s1516-35982012000400023
|View full text |Cite
|
Sign up to set email alerts
|

Rendimento, composição e análise sensorial do queijo minas frescal fabricado com leite de vacas mestiças alimentadas com diferentes volumosos

Abstract: Holstein/Gir crossbred cows, with lactation period of 180 ± 12 days were distributed in two 4 × 4 latin squares (four animals, four diets and four periods). The experimental periods had a duration of 18 days: 15 days of adaptation and three days of data collection. After cheese processing microbiological, physical-chemical and sensory analysis were done. Cheese samples were frozen and analyzed for fatty acid profile. The fat content of cheese was higher for diets with sugar cane and sunflower silage compared w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 29 publications
0
3
0
1
Order By: Relevance
“…TDE is very important in the production of whey derivatives and other foods that use it in their composition, such as cakes, meat products, such as mortadella, and derivatives, such as ricotta and dairy beverages, whose functional and nutritional characteristics reflect the quality of the whey [49,50]. The TSE values found in this study are generally below those described in the literature, since contents between 11.0% and 13.0% are mentioned [51,52].…”
Section: Resultscontrasting
confidence: 49%
“…TDE is very important in the production of whey derivatives and other foods that use it in their composition, such as cakes, meat products, such as mortadella, and derivatives, such as ricotta and dairy beverages, whose functional and nutritional characteristics reflect the quality of the whey [49,50]. The TSE values found in this study are generally below those described in the literature, since contents between 11.0% and 13.0% are mentioned [51,52].…”
Section: Resultscontrasting
confidence: 49%
“…Oetker Powder Tasteless Colorless Gelatin), and standardized pasteurized milk (brand CompLeite) with a fat content of 3% were obtained from retail market in the city of Goiania, GO. The whey was obtained according to the methodology described by Alves (2010), Hofmeister et al (2005) and Martins et al (2012) with some modifications. The protocol followed was as follows: heating of pasteurized whole milk to 35 °C, addition of calcium chloride (50% solution) and liquid rennet, resting for 50 minutes, coagulation and mass cutoff point test, slowly cutting the mass and getting large cubes (grain no.…”
Section: Raw Materialsmentioning
confidence: 99%
“…In evaluating crossbred dairy cows, Martins et al (2012) reported the influence of genetic composition and production level on milk composition, particularly on the levels of fat, protein and total solids. The analysis of physical and chemical composition of genotype 5 milk (Girolando ¾ and Holstein -pure) was, in a way, compromised by the fact that milk coming from two genetic groups that produce milk with different compositions had been mixed in the same tank.…”
Section: Resultsmentioning
confidence: 99%